E-Flashcard Media Development Using Application Of Assemblr Edu On The Material On The Relationship Of Pancasila Values In Daily Life Practice - Mira Mirawati; Wawan Syahiril Anwar; Jaja Sudarjat; Tiara Yuniar Christin; Cindy Aulia Ramita; Nurmasari Situmeang (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This research aims to develop E-Flashcard media using the Assemblr EDU application and test its feasibility on material on the relationship between Pancasila values in daily life practice. The research uses the Research and Development (R&D) method with the ADDIE model, but the implementation is limited to the implementation stage. The research subjects consisted of three expert validator lecturers (media, language, and materials) and one teacher of material experts and 23 students of grade VI of SD Negeri Lawanggintung 2 Bogor City. Data collection techniques were carried out through questionnaires, interviews, and documentation, while data analysis used qualitative and quantitative approaches with a Likert scale. The results of the study showed that the developed media obtained a very decent category with a validation percentage above 90%. The response of students was 87% and the teacher's response of 92.18% was in the very good category. This media also shows a high level of interest, ease of use, interactivity, and motivation to learn so that the E-Flashcard media using the Assemblr EDU application is declared suitable for use in learning on the material on the relationship between Pancasila values in daily life practice.